Factors Affecting Adaptability of Cryptocurrency: An Application of Technology Acceptance Model - Erlangga Dwi Apriliansyah; Adi Setiawan (Journal of World Science, 2026)
The transition to a digital financial system, including the presence of cryptocurrencies, requires further exploration of the determinants of its adoption. This study analyzes the role of technology awareness and government support for use intent by utilizing the Technology Acceptance Model (TAM) framework which is extended through mediation variables: perception of benefit, convenience, and risk. Through an explanatory quantitative approach, data was collected from 190 millennial and Z participants in Indonesia using the snowball sampling technique. Path analysis is performed using IBM AMOS. The results confirm that technology awareness and government support are significant in shaping perceptions of benefits, convenience, and risks (H1–H6 supported). However, the three mediation variables did not have a significant effect on the behavioral intention in adopting crypto (H7–H9 was rejected). These findings suggest that crypto adoption among Indonesia's younger generation is driven more by non-technical factors such as Fear of Missing Out (FOMO) and short-term speculative motives, rather than rational considerations regarding the benefits of technology. Implicitly, FinTech regulators and service providers need to develop educational strategies that emphasize risk literacy more than just the technical aspects of the application.